Pengaruh Kualitas Layanan Farmasi dan Citra Rumah Sakit Terhadap Kepuasan Pasien dan Dampaknya Pada Loyalitas Pasien (Studi pada Pasien Rawat Jalan Rsud Ratu Aji Putri Botung Kalimantan Timur) - Ruk’at Rukmayanti; Taufik Zulfikar; Chevie Wirawan (Universitas Pahlawan Tuanku Tambusai, 2025)
Patient satisfaction is not merely the ultimate goal of quality service, but also a bridge to patient loyalty. Patient loyalty is crucial for the long-term operational sustainability and growth of a hospital. This study aims to determine the influence of pharmaceutical service quality and hospital image on patient loyalty, mediated by patient satisfaction. The research was conducted at RSUD Ratu Aji Putri Botung, with a sample of 98 respondents selected using a purposive sampling technique. Data were collected through a survey utilizing a 1-5 Likert scale instrument. The statistical analysis employed descriptive statistics and hypothesis testing using Structural Equation Modeling - Partial Least Square (SEM PLS). The results of the SEM PLS analysis indicate that the model's goodness of fit is acceptable, as shown by an R-squared value above 50% (categorized as a medium to high influence), a high Q-squared predict value (>50%), a GoF index of 0.664 > 0.36 (categorized as high GoF), and PLS Predict and CVPAT indicating high predictive power. The outer model evaluation confirmed acceptable levels of validity and reliability. The study's findings reveal that pharmaceutical service quality and hospital image positively impact patient satisfaction, and subsequently, patient loyalty.